OPTIMALISASI LAHAN MARGINAL UNTUK PENINGKATAN EKONOMI PERTANIAN MELALUI INDUSTRIALISASI PRODUK TANAMAN GAMAL DI DESA TEUPIN PANAH KECAMATAN KAWAY XVI - Saputra, Arie; Fitriadi, fitriadi; Muzakir, Muzakir; Syahril, Syahril; Fadhlain, Said; hadi, khairul; noviar, helmi (Jurnal Pengabdian Agro and Marine Industry, 2025)
West Aceh has great natural resource potential, but land utilization is still low due to limited infrastructure, low land management skills, and social and environmental factors. This program proposes the industrialization of Gamal plants (Gliricidia sepium) as a solution to optimize marginal land. Gamal plants are chosen because of their adaptive, multifunctional nature, and ability to increase soil fertility naturally. This service uses the Participatory Rural Appraisal (PRA) and Community-Based Empowerment approaches and is carried out in Teupin Panah Village, Kaway XVI District, West Aceh, as a pilot project. Activities include socialization, cultivation training, and distribution of Gamal seeds. The results of the activities show that Gamal cultivation can increase the utilization of idle land, provide alternative sources of animal feed, produce bioenergy, and improve environmental quality. The economic value of this cultivation is potential, with an income of up to IDR 45 million per hectare per year. This program also increases local communities' awareness and skills in sustainable land management.